2015
DOI: 10.1039/c4ra15650a
|View full text |Cite
|
Sign up to set email alerts
|

Structure resembling effect of clay surface on photochemical properties of meso-phenyl or pyridyl-substituted monocationic antimony(v) porphyrin derivatives

Abstract: Four types of meso-phenyl or pyridyl-substituted monocationic antimony(V) porphyrin derivatives (Sb V Pors)-5, 10,15,20-tetraphenyl; 5,10,15-triphenyl-20-mono(4-pyridyl); 5,15-diphenyl-10,20-di(4pyridyl); and 5,10,15,20-tetra(4-pyridyl)porphyrinato dihydroxo antimony(V) chloride-with different hydrophobicities were synthesised, and their photochemical properties on anionic clay were investigated. The absorption and fluorescence behaviour of the Sb V Pors were strongly affected by complex formation with clay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…properties of antimony compounds in inorganic and organic compounds have been studied in the past. [51][52][53] As long as Sb is present and keeps absorbing photons, it will probably emit photons too. Fluorescence measurements were not carried out in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…properties of antimony compounds in inorganic and organic compounds have been studied in the past. [51][52][53] As long as Sb is present and keeps absorbing photons, it will probably emit photons too. Fluorescence measurements were not carried out in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…For many dye molecules, an increase in the transition probability on the saponite surface has been observed. This effect would be induced by an increase in the Franck–Condon factor due to resembling of the molecular structures of the ground and excited states. , In this study, the ∫εdv̅ values of m -B III TMPySp and p -B III TMPySp with the saponite increased about 1.05 and 1.14 times compared to those in the bulk solution, respectively (Table ).…”
Section: Results and Discussionmentioning
confidence: 54%
“…Recently, we have reported that particular multicationic and planar dye molecules, such as +4-charged porphyrins, could be strongly adsorbed on the clay surface by a strong electrostatic interaction. For such molecules, photophysical properties, such as fluorescence quantum yields or lifetimes have been enhanced because of fixation of the molecular structures onto the clay surface and/or suppression of aggregation and self-fluorescence quenching. Especially, in the case that the distance between positive charges in the guest molecules and an average negative charge distance on the clay surface coincide well, the guest molecules can be adsorbed up to high density without aggregation because Coulomb’s force is strengthened especially in such conditions (size-matching rule). …”
Section: Introductionmentioning
confidence: 99%
“… 29 , 42 Several studies have reported that the major factor for the fluorescence enhancement is a fixation of rotational substituents. 21 , 22 Thus, a strong fixation of Acr on the hydrophobic clay surface, suppressing the rotation of the substituent, could be a reason why the hydrophobic clay induced the large fluorescence enhancement, as in the case with the discussion for the Stokes shift.…”
Section: Resultsmentioning
confidence: 88%